Clinical effect and cost-effectiveness of incorporation of point-of-care assays into early infant HIV diagnosis programmes in Zimbabwe: a modelling study. Issue 3 (March 2019) - Frank, Simone C; Cohn, Jennifer; Dunning, Lorna; Sacks, Emma; Walensky, Rochelle P; Mukherjee, Sushant; Dugdale, Caitlin M; Turunga, Esther; Freedberg, Kenneth A; Ciaranello, Andrea L
Summary: Background: New point-of-care (POC) assays for early infant HIV diagnosis are costlier than conventional total nucleic acid assays, but could increase access to testing, shorten time to results, and expedite initiation of antiretroviral therapy. We aimed to assess the clinical benefits and cost-effectiveness of incorporating these POC assays into early infant diagnosis programmes in Zimbabwe. Methods: We used the Cost Effectiveness of Preventing AIDS Complications (CEPAC)—Pediatric model to examine the clinical benefits, costs, and cost-effectiveness of replacing conventional assays for early infant HIV diagnosis with POC assays at age 6 weeks in Zimbabwe. We simulated two strategies for early infant HIV diagnosis: conventional and POC. Modelled assays differed in sensitivity; specificity; time to, and probability of, return of results; and cost. Model outcomes included survival, life expectancy, and mean lifetime per-person treatment cost, which were reported separately for all HIV-exposed infants and all infants with HIV. We calculated incremental cost-effectiveness ratios with discounted (3% per year) costs and life expectancy from a health-care system perspective for all HIV-exposed infants. We judged incremental cost-effectiveness ratios of 1010 (Zimbabwe's annual gross domestic product per person) or less per year of life saved to be cost-effective. Findings: When conventional assays were used for early infant diagnosis, projected undiscounted life expectancy was 22·7 years for infants with HIV and 62·5 years for all HIV-exposed infants, at a cost of 610 per HIV-exposed infant. Use of POC assays for early infant HIV diagnosis improved projected undiscounted life expectancy to 25·5 years among infants with HIV and 62·6 years among HIV-exposed infants at a cost of 690 per HIV-exposed infant. At age 12 weeks, survival among all infants with HIV was 76·1% with the conventional testing strategy and 83·5% with the POC testing strategy. The incremental cost-effectiveness ratio of POC assays versus conventional assays for early infant diagnosis was 680 per year of life saved. When conventional assay characteristics remained constant, this ratio remained under the cost-effectiveness threshold as long as the specificity and sensitivity of the POC assay were greater than 92% and 65%, respectively. Our results were robust to plausible variations in POC assay cost, the probability of ART initiation, and probability of return of the results of POC testing. Interpretation: Compared with conventional assays, POC assays for early infant HIV diagnosis in Zimbabwe will improve survival, extend life expectancy, and be cost-effective for HIV-exposed infants. Funding: Elizabeth Glaser Pediatric AIDS Foundation, US National Institute of Allergy and Infectious Diseases, Eunice Kennedy Shriver National Institute of Child Health and Human Development, and Unitaid.